Responding to the Coronavirus Pandemic: A Tale of Two Cities. Issue 6 (August 2020) - Weng, Shi-Hong; Ni, Anna Ya; Ho, Alfred Tat-Kei; Zhong, Ruo-Xi
This study compares the experiences of Shanghai in China and Los Angeles in the United States to illustrate four tension points in pandemic responses: immediacy versus thoroughness, transparency versus secrecy and security, centralization versus decentralization, and state-driven solutions versus coproduction. Based on the case analysis, strategic management and planning practices in six stages of pandemic response are recommended. The study also suggests research questions for future comparative research to examine more carefully how pandemic responses should vary due to institutional differences and local contextualization and adaptation.